A new species of the small water strider genus Microvelia (Hemiptera: Heteroptera: Veliidae) from the Ryukyus, Japan, with notes on the distribution of M. kyushuensis - Aiso, Takumi; Ishikawa, Tadashi (Zootaxa, 2024)
A new species of the small water strider genus Microvelia Westwood, 1834, M. minsa sp. nov. (Hemiptera: Heteroptera: Veliidae), is described from the Yaeyama Islands of the Ryukyus, Japan. It belongs to the subgenus Pacificovelia Andersen & Weir, 2003. This new species has long been confused with M. kyushuensis Esaki & Miyamoto, 1955, in Japan, but is distinguished from the latter by a larger and more slender body approximately 2.5 times as long as its maximum width, a pair of square gray to grayish-blue markings on abdominal mediotergites II, III, and V, and the male right paramere evenly curved with the apical half twisted.